Sifat Fisis Dan Keunggulan Papan Semen Dari Limbah Kulit Batang Sagu - Maail, Rohny S.; Derlauw, Irfan (MAKILA, 2019)
This research aimed to determine the physical properties and advantages of cement boards made from sago stem bark waste based on the test results of several parameters, according to JIS A 5908 (2003) standard. The results show that the physical properties of cement board from sago stem bark waste with the addition of the CaCl2 catalyst were good with the average value of cement board density ranged from 1.19-1.26 gr/cmÂ³, water content 7,67-8,02%, water absorption after immersion 2 hours 6,03-7.65% and after 24-hour immersion 11,62-12,91%, respectively. The averages swelling value of board thickness after immersion 2 hours 1.62-12,91% and after immersion 24 hours 1.40-3.41%. Furthermore, sago bark waste in various positions of the tree trunk (tree base, middle, and top) can be utilized to manufacture the cement board. However, the board made from sago stem bark waste at the ground with the addition of a catalyst CaCl2 6% has the best physical properties and meets JIS A 5908 (2003) standard. Cement boards from sago stem bark waste have an excellent waterproof capability and can be used as outdoor materials.